Southern Pride as Reflected in Tennessee Williams’ The Glass Menagerie - Tini Mogea (Student Scientific Creativity Journal, 2023)
This research is mainly intended to reveal the old southern pride reflected in the characteristics of Amanda, a southern lady. In conducting this research, the writer uses qualitative research, in which the data are collected in the form of words and the writer is the key instrument. The data were taken from the work itself and other relevant books supporting the data. In analyzing the data, the writer uses a mimetic approach, which considers that literary work is a reflection and imitation of aspects of the universe. The result of this research shows that in the southern part of America before the Civil War, there was a custom called "southern gentility." This is one of the aristocratic values that consists of the manner of speech, the way of wearing the clothes, and the manner of treating the caller: the way to welcome and praise the gentleman caller, his wealth, and his beauty. This southern gentility represents old southern pride or honor. These values are reflected in Amanda’s attitude as an old southerner. However, a change in period is followed by a change in values; the aristocratic values mentioned above are no longer all relevant to the new South’s way of life because they faded away after the Civil War in 1861-1865. Amanda, as an old southerner, has always held these values; however, realizing that they are no longer applicable in the present, she attempts to adapt the new southern values. Yet, she is too late to adjust because her son, who possesses new southern values, refuses to accept her advice, so he runs away.